"Accentuate the Positive; Eliminate the Negative": Hegemonic Interest Convergence, Racialization of Latino Poverty, and the 1968 Bilingual Education Act. Issue 3 (27th May 2017) - Sung, Kenzo K.
Abstract : Derrick Bell's interest convergence thesis is a seminal framework to analyze social change within critical race theory. While interest convergence's influence has grown, two foundational questions have been raised: do interest groups act rationally; does interest convergence also offer a change prescription or only an explanation of prior events. By revisiting Bell's early influences, via the concept of hegemony, the article intervenes in these two formative debates by offering a reimagined analytic framing that I term "hegemonic interest convergence." The article then applies this concept to analyze how broader political economic shifts shaped the struggles within which the 1968 Bilingual Education Act arose. I demonstrate that support for bilingual education stemmed from a seeming interest convergence among policymakers and Latino activists based on economic, rather than cultural, concerns regarding poor urbanizing Latino communities. In doing so, policymakers promoted the bill as a concession to redirect focus from other Latino demands for economic uplift and a tool to promote ideas of cultural deficit that reimagined job automation and outsourcing into linguistic and racial "handicaps." These findings are significant in illuminating how hegemonic interest convergence functions, thereby providing a novel historiographical analysis of the Bilingual Education Act as well as suggesting a possible strategy for future change.